Assessing the benefits of international portfolio diversification in bonds and stocks. - Roberto A. De Santis; Lucio Sarno (European Central Bank (ECB), 2008)
This paper considers a stylized asset pricing model where the returns from exchange rates, stocks and bonds are linked by basic risk-arbitrage relationships. Employing GMM estimation and monthly data for 18 economies and the US (treated as the domestic country), we identify through a simple test the countries whose assets strongly comove with US assets and the countries whose assets might other larger diversification benefits. We also show that the strengthening of the comovement of returns across countries is neither a gradual process nor a global phenomenon, reinforcing the case for international diversification. However, our results suggest that fund managers are better other constructing portfolios selecting assets from a subset of countries than relying on either fully inter-nationally diversified or purely domestic portfolios.
Keywords: F31; G10; 330; asset pricing; Exchange Rates; international parity conditions; market integration; stochastic discount factor; Aktienmarkt; Rentenmarkt; Devisenmarkt; Kapitaleinkommen; Konjunkturzusammenhang; Portfolio-Management; Industrieländer